Strain-specific differences in pili formation and the interaction of Corynebacterium diphtheriae with host cells - Ott, Lisa; Höller, Martina; Rheinlaender, Johannes; Schäffer, Tilman; Hensel, Michael; Burkovski, Andreas (BMC Microbiology, 2010)
Background: Corynebacterium diphtheriae, the causative agent of diphtheria, is well-investigated in respect to toxin production, while little is known about C. diphtheriae factors crucial for colonization of the host. In this study, we investigated strain-specific differences in adhesion, invasion and intracellular survival and analyzed formation of pili in different isolates. Results: Adhesion of different C. diphtheriae strains to epithelial cells and invasion of these cells are not strictly coupled processes. Using ultrastructure analyses by atomic force microscopy, significant differences in macromolecular surface structures were found between the investigated C. diphtheriae strains in respect to number and length of pili. Interestingly, adhesion and pili formation are not coupled processes and also no correlation between invasion and pili formation was found. Using RNA hybridization and Western blotting experiments, strain-specific pili expression patterns were observed. None of the studied C. diphtheriae strains had a dramatic detrimental effect on host cell viability as indicated by measurements of transepithelial resistance of Detroit 562 cell monolayers and fluorescence microscopy, leading to the assumption that C. diphtheriae strains might use epithelial cells as an environmental niche supplying protection against antibodies and macrophages. Conclusions: The results obtained suggest that it is necessary to investigate various isolates on a molecular level to understand and to predict the colonization process of different C. diphtheriae strains. © 2010 Ott et al; licensee BioMed Central Ltd.
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.IAP.LAP.strain